Progression of myocardial dysfunction and prediction of arrhythmic events in patients with exercise-induced arrhythmogenic cardiomyopathy - Linda T. Aaserud, MD; Christine Rootwelt-Norberg, MD, PhD; Christian K. Five, MD; Eivind W. Aabel, MD, PhD; Nina E. Hasselberg, MD, PhD; Erik Lyseggen, MD, PhD; Kristina H. Haugaa, MD, PhD; Øyvind H. Lie, MD, PhD (Heart Rhythm O2, 2024)
Background: Several reports exist of an acquired exercise-induced arrhythmogenic cardiomyopathy. Little is known about myocardial disease progression and arrhythmia prediction in this population. Objective: The study sought to explore the evolution of myocardial function and structure and its relation to incident life-threatening ventricular arrhythmias (VA), to identify markers of impending events. Methods: We included athletes (individuals with exercise doses >24 metabolic equivalent of task hours per week, >6 consecutive years, participating in organized and competitive sports) who had VA, absence of family history and known genetic variants associated with cardiac disease, and no other identified etiology, in a tertiary referral single-center, longitudinal cohort study of patients with exercise-induced arrhythmogenic cardiomyopathy (EiAC). Evolution of myocardial function and structure was assessed by repeated echocardiographic examinations during long-term follow-up. Life-threatening VA were assessed at baseline and during long-term follow-up. Results: Forty-one EiAC patients (15% women, age 45 ± 13 years) were followed for 80 (interquartile range 48–115) months. There were no changes in myocardial function or structure in the overall population during follow-up. We observed high incidence rate and high recurrence rate of life-threatening VA in EiAC patients. Subtle deterioration of right ventricular function was strongly associated with subsequent first-time VA (odds ratio 1.12, 95% confidence interval 1.01–1.25, P = .031, per 1% deterioration of right ventricular free wall longitudinal strain). Conclusion: There were no clear changes in myocardial function or structure during follow-up in the overall population, but there was a high incidence rate and high recurrence rate of life-threatening VA. Subtle right ventricular deterioration by free wall longitudinal strain was a strong predictor of impending first-time life-threatening VA during follow-up.